ARM-Cortex Based Control System to Generate Attendance Monitoring System - Yadav, Amit Kumar (International Journal of Computer Sciences and Engineering, 2025)
The paper presents modelling and implementation of an automated system which can be used to generate attendance monitoring system. ARM NXP CORTEX-M3 LPC1768 version is employed in which RFID module is interfaced along the controller to track the number of absent and present students. The detailed information about the student can be seen on the central computer system as a single application created on Visual Basic which thus can be printed.